Penambahan Level Ekstrak Wortel (Daucus carota) pada Pengencer Andromed Dalam Mempertahankan Kualitas Spermatozoa Sapi Bali pada Suhu 5 OC - Yuni Mariani; Alimuddin Alimuddin (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
A good diluents must have the ability to reduce the rate of decline in the quality of spermatozoa, by choosing the right diluents that is able to maintain the quality of spermatozoa. The addition of antioxidants is believed to be able to maintain spermatozoa life longer, one of which is the addition of carrot extract. The purpose of this study was to maintain the quality of Bali cattle spermatozoa stored at 5 0C by utilizing the quality of bali cattle spermatozoa because they contain antioxidants. This study used a completely randomized design (CRD) consisting of 5 treatments and 5 replications, namely: P0 = cement + andromed, P1 = cement + andromed + 5 % carrot extract, P2 = cement + andromed + 10 % carrot extract, P3 = cement + andromed + 15 % carrot extract, P4 = cement + andromed + 20 % carrot extract. The variables measured were the quality of the spermatozoa microscopically, namely the motility and viability of the spermatozoa. The result showed that the increase in the level of carrot extract in andromed diluent in maintaining spermatozoa motility at 5 0C was not significant (P>0,05), meaning that each treatment had the same effect in maintaining spermatozoa motility. The percentage of motility in all treatments is feasible to be applied to the IB program because is still shows a value of more than 40 %.